2021
DOI: 10.21203/rs.3.rs-846195/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Phylogenies Map to Biogeography Better than Morphological Ones

Abstract: Phylogenetic relationships are inferred principally from two classes of data: morphological and molecular. Most current phylogenies of extant taxa are inferred from molecules, and when morphological and molecular trees conflict the latter are often preferred. Although supported by simulations, the superiority of molecular trees has never been assessed empirically. Here we test phylogenetic accuracy using two independent data sources: biogeographical distributions and fossil first occurrences. For 48 pairs of m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…They were able to show that morphological data were more prone to convergence than amino acid sites, in large part due to the small number of character states defined for discretized morphological characters. Similarly, in the case of biogeography, a recent meta-analysis of morphological and molecular phylogenies showed that molecular phylogenies exhibit better congruence to biogeographic distributions than their counterpart morphological trees [87], suggesting that homoplasy in morphological trees obscures inference of macroevolutionary processes.…”
Section: Morphology In the Era Of Phylogenomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were able to show that morphological data were more prone to convergence than amino acid sites, in large part due to the small number of character states defined for discretized morphological characters. Similarly, in the case of biogeography, a recent meta-analysis of morphological and molecular phylogenies showed that molecular phylogenies exhibit better congruence to biogeographic distributions than their counterpart morphological trees [87], suggesting that homoplasy in morphological trees obscures inference of macroevolutionary processes.…”
Section: Morphology In the Era Of Phylogenomicsmentioning
confidence: 99%
“…Yet few published works arrive at this explicit conclusion. The archetypal conclusions postulated by phylogenetic workers that compare data classes to the detriment of morphology are (1) the importance of fossils and an integrated understanding of evolutionary history, which substantiates the continued relevance of morphology (e.g., [67,87,88]); and/or (2) a call for collecting more morphological data, despite the molecular data usually having resolved most of the relationships in question more efficiently and more reproducibly (e.g., [60]). Given the comparatively greater epistemological and practical challenges to collecting, interpreting, and analyzing morphological data in the context of phylogenetic inference, it is not surprising that morphological datasets have taken on an ancillary role by comparison to molecular data, in deciphering evolutionary relationships of extant taxa.…”
Section: Morphology In the Era Of Phylogenomicsmentioning
confidence: 99%
“…Morphological affinities are considered insufficient for testing evolutionary hypotheses because of interference from homoplasy and convergence 65 . The scarcity of genetic data in our research, which could serve for haplotype and private allele inquiry, hamper inferences concerning the radiation of taxa grouped in specific clades.…”
Section: Phylogenymentioning
confidence: 99%